2019
DOI: 10.1053/j.gastro.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nucleic Acids Are Associated With Outcomes of Patients With Pancreatic Cancer

Abstract: In a prospective cohort of pancreatic cancer patients, we show how longitudinal monitoring using liquid biopsy samples through exoDNA and ctDNA provides both predictive and prognostic information relevant to therapeutic stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
294
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(313 citation statements)
references
References 37 publications
6
294
1
Order By: Relevance
“…Other studies demonstrated that, among various cancer types, concordance was variable with a range of ~70–98%, depending on the gene(s) examined . Several previous studies evaluated the concordance of KRAS alterations between tissue and ctDNA and found overall concordance to range 67–96% . These studies did not evaluate the impact of time interval between tissue biopsy and blood draw, nor did they examine the correlation with site of biopsy or the association with outcome for discordant vs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated that, among various cancer types, concordance was variable with a range of ~70–98%, depending on the gene(s) examined . Several previous studies evaluated the concordance of KRAS alterations between tissue and ctDNA and found overall concordance to range 67–96% . These studies did not evaluate the impact of time interval between tissue biopsy and blood draw, nor did they examine the correlation with site of biopsy or the association with outcome for discordant vs .…”
Section: Introductionmentioning
confidence: 99%
“…8,14,15 Several previous studies evaluated the concordance of KRAS alterations between tissue and ctDNA and found overall concordance to range 67-96%. 6,[16][17][18] These studies did not evaluate the impact of time interval between tissue biopsy and blood draw, nor did they examine the correlation with site of biopsy or the association with outcome for discordant vs. concordant KRAS alterations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bernard et al . () analyzed longitudinal KRAS mutant allele fraction from ctDNA and exosome DNA and determined that longitudinal monitoring through exosome DNA rather than ctDNA provides prognostic information.…”
Section: Clinical Application Of Ctdna In Pdacmentioning
confidence: 99%
“…A recent meta-analysis by Creemers et al (2017) showed that the ctDNA in pancreatic cancer is significantly associated with a poor prognosis. In contrast, Bernard et al (2019) analyzed longitudinal KRAS mutant allele fraction from ctDNA and exosome DNA and determined that longitudinal monitoring through exosome DNA rather than ctDNA provides prognostic information.…”
Section: Prognostic Markermentioning
confidence: 99%
“…These existing data, which may be leveraged to guide treatment sequencing, are clearly rudimentary. However, we and others are investigating assays of circulating tumor cells, nucleic acids, and exosomes that may quantify and characterize occult metastatic disease and more accurately predict the role of local therapies . Our group also has defined an imaging biomarker that can be evaluated using routine computed tomographic images and may be used to stratify patients’ tumors into distinct biophysical subtypes .…”
Section: Comparison Of Possible Trial Designs For Patients With Brpcmentioning
confidence: 99%